Sistem Pengepakan Dengan Metode Sortasi Pengaturan Kecepatan Konveyor Berdasarkan Ukuran Kemasan Menggunakan Outseal PLC Nano V.4 Dan Haiwell SCADA - Wahyudi, Erik; Amri, Hikmatul; Syarif, Irwan (Department of Electrical Engineering, University of Patria Artha, 2020)
The production process which is designed is a packaging system for the initial storage of products to be filled in the packaging, in this study a conveyor is designed that can sort objects using a proximity sensor and adjust the speed based on the size of the packaging using pulse width modulation (PWM), and can fill the packaging based on the size of the packaging. The product. Automatic control of packing using Outseal PLC Nano.V.4, the system can be controlled and monitored using Haiwell SCADA software on a PC. Outseal PLC nano V.4 test results can operate based on program commands that have been designed. The use of PWM Outseal PLC Nano V.4 on a 12 volt DC motor as a speed controller works in accordance with the duty cycle and PWM scale values given with an efficiency value of 86,56 % at at a PWM value of 900 and 86,23 % at a PWM value of 1023. HMI system made using Haiwell SCADA to control and monitor a successful packing system. Outseal PLC Nano V.4 can operate optimally with the SCADA system. The overall system test results of all sensor components, product packaging and HMI variables are 100 % successful, with an average processing time of packing size M for 11.62 seconds and size L for 14.58 seconds.